Will the bridge get us there? narrowing the gap between formal and nonformal education - Ulep, Myrna P. (2006)
The study aimed to determine the strengths and weaknesses of the Re-entry Education Agenda for the Poor Program of Angelicum College to meet the learning needs of its clientele. It resorted to a qualitative inquiry using a case study approach. Documents from Angelicum College were retrieved and the learning site revisited to determine the implementation process, enrollment, retention, and attrition. Findings showed that the program's strength lies in its nondiscrimination of learners, its flexible and resource-saving delivery system, and its provision for re-entry. However, it is too prescriptive, academic, and rigid for its target clientele. Angelicum College has to look into its curricular offerings and incorporate the learners' lived experiences to make the program more relevant and useful to REAP learners.